Clinical features of pediatric patients with coronavirus disease (COVID-19) (2020)
Background Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has spread around the world, and reports of children with COVID-19 are increasing. Objectives To assess clinical profiles of pediatric COVID-19. Study design A retrospective analysis was undertaken using clinical data of sixteen children (11 months-14 years) diagnosed with COVID-19 between January 1, 2020 and March 17, 2020 at Xiangyang Central Hospital, Hubei province, China. Results All children had positive epidemiologic histories, 12 (12/16, 75 %) involving family units. The illnesses were either mild (5/16, 31.3 %) or ordinary (11/16, 68.8 %), presenting as follows: asymptomatic (8/16, 50 %), fever and/or cough (8/16, 50 %). Four asymptomatic patients (4/16, 25 %) in ordinary cases had chest computed tomography (CT) abnormalities. Leukocyte counts were normal in 14 cases(88 %), but 2 patients (12.5 %) had leukopenia, and 1 (6.3 %) was lymphopenic. There were 11 patients with chest CT abnormalities, some nodular, others small patchy and others ground-glass opacities. In asymptomatic children, the median time to SRAS-CoV-2 nucleic acid test(NAT) positivity once exposed to a family member with confirmed infection was 15.5 days (range, 10–26 days). The median time to first NAT-negative conversion was 5.5 days (range, 1–23 days). Conclusions COVID-19 in children of Xiangyang city is often family acquired and not serious, with favorable outcomes. Asymptomatic children can be diagnosed as pneumonia because of chest CT abnormalities. It is essential to actively screen this segment of the population.